Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Let's analyze the given explicit formula for the sequence:
[tex]\[ f(n) = 70(-2)^{n-1} \][/tex]
We want to convert this explicit formula into a recursive formula, which means expressing [tex]\( f(n) \)[/tex] in terms of [tex]\( f(n-1) \)[/tex].
First, let's observe the pattern:
- The first term [tex]\( f(1) \)[/tex] when [tex]\( n = 1 \)[/tex] is:
[tex]\[ f(1) = 70(-2)^{1-1} = 70(-2)^0 = 70 \cdot 1 = 70 \][/tex]
- The second term [tex]\( f(2) \)[/tex] when [tex]\( n = 2 \)[/tex] is:
[tex]\[ f(2) = 70(-2)^{2-1} = 70(-2)^1 = 70 \cdot (-2) = -140 \][/tex]
- The third term [tex]\( f(3) \)[/tex] when [tex]\( n = 3 \)[/tex] is:
[tex]\[ f(3) = 70(-2)^{3-1} = 70(-2)^2 = 70 \cdot 4 = 280 \][/tex]
- The fourth term [tex]\( f(4) \)[/tex] when [tex]\( n = 4 \)[/tex] is:
[tex]\[ f(4) = 70(-2)^{4-1} = 70(-2)^3 = 70 \cdot (-8) = -560 \][/tex]
Now, let's analyze the relationship between consecutive terms. We notice that:
[tex]\[ \begin{aligned} f(2) &= -2 \cdot f(1) & = -2 \cdot 70 & = -140 \\ f(3) &= -2 \cdot f(2) & = -2 \cdot (-140) & = 280 \\ f(4) &= -2 \cdot f(3) & = -2 \cdot 280 & = -560 \end{aligned} \][/tex]
Therefore, we can see a clear pattern where each term is obtained by multiplying the previous term by -2.
Thus, the recursive formula for [tex]\( n > 1 \)[/tex] is:
[tex]\[ \begin{aligned} f(1) &= 70 \\ f(n) &= -2 \cdot f(n-1) \quad \text{for} \quad n > 1 \end{aligned} \][/tex]
From the given choices, the correct recursive formula is:
[tex]\[ f(n) = -2 \cdot f(n-1) \quad \text{for} \quad n > 1 \][/tex]
Hence, the correct answer is:
[tex]\[ f(n) = -2 f(n-1) \][/tex]
[tex]\[ f(n) = 70(-2)^{n-1} \][/tex]
We want to convert this explicit formula into a recursive formula, which means expressing [tex]\( f(n) \)[/tex] in terms of [tex]\( f(n-1) \)[/tex].
First, let's observe the pattern:
- The first term [tex]\( f(1) \)[/tex] when [tex]\( n = 1 \)[/tex] is:
[tex]\[ f(1) = 70(-2)^{1-1} = 70(-2)^0 = 70 \cdot 1 = 70 \][/tex]
- The second term [tex]\( f(2) \)[/tex] when [tex]\( n = 2 \)[/tex] is:
[tex]\[ f(2) = 70(-2)^{2-1} = 70(-2)^1 = 70 \cdot (-2) = -140 \][/tex]
- The third term [tex]\( f(3) \)[/tex] when [tex]\( n = 3 \)[/tex] is:
[tex]\[ f(3) = 70(-2)^{3-1} = 70(-2)^2 = 70 \cdot 4 = 280 \][/tex]
- The fourth term [tex]\( f(4) \)[/tex] when [tex]\( n = 4 \)[/tex] is:
[tex]\[ f(4) = 70(-2)^{4-1} = 70(-2)^3 = 70 \cdot (-8) = -560 \][/tex]
Now, let's analyze the relationship between consecutive terms. We notice that:
[tex]\[ \begin{aligned} f(2) &= -2 \cdot f(1) & = -2 \cdot 70 & = -140 \\ f(3) &= -2 \cdot f(2) & = -2 \cdot (-140) & = 280 \\ f(4) &= -2 \cdot f(3) & = -2 \cdot 280 & = -560 \end{aligned} \][/tex]
Therefore, we can see a clear pattern where each term is obtained by multiplying the previous term by -2.
Thus, the recursive formula for [tex]\( n > 1 \)[/tex] is:
[tex]\[ \begin{aligned} f(1) &= 70 \\ f(n) &= -2 \cdot f(n-1) \quad \text{for} \quad n > 1 \end{aligned} \][/tex]
From the given choices, the correct recursive formula is:
[tex]\[ f(n) = -2 \cdot f(n-1) \quad \text{for} \quad n > 1 \][/tex]
Hence, the correct answer is:
[tex]\[ f(n) = -2 f(n-1) \][/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.